Sifat Fisik Gel Masker Peel off Sari Cucumis Sativus dengan Basis Polivinil Alkohol dan Variasi Konsentrasi Hidroksipropil Metilselulosa - Fitriyani, Neng Yasmi Bella; Nurul (LP4M STIKes Karsa Husada Garut, 2023)
Introduction: Cucumber is a type of fruit from the gourd family (Cucurbitaceae). Cucumber has a high water content, provides a sensation of freshness, and has cooling and soothing properties on irritated skin. Peel off masks are vinyl-based formulations with advantages such as ease of use, easy rinsing and cleaning. In this study, cucumber juice can to add to the peel off mask formulation. This study evaluated the physical properties of peel off masks with polyvinyl alcohol base and varying concentrations of hydroxypropyl methylcellulose Method: The design of this study was descriptive quantitative to assess the physical properties of peel off masks. Results: The results showed that variations in PVA and HPMC bases did not affect color, odor, or taste, but only affected texture. Each formulation has a thick to thin texture. The homogeneity of the mask was not affected by the variation of PVA and HPMC bases, the pH of the preparation remained unchanged. Spreadability and dry time were affected by HPMC concentration, with smaller concentrations resulting in shorter spreadability and longer dry time. Viscosity values decreased with different stirring speeds. Conclusion: The peel off masks have relatively similar organoleptical physical properties and pH in each formula, except for diverse textures, while the concentration of PVA and HPMC is directly proportional to the dry time, spreadability and viscosity of cucumber juice peel off masks.